In-vitro Bactericidal Activity of a Novel Plant Source Plumeria pudica against Some Human and Fish Pathogenic Bacteria - Das, Shubhaisi; Burman, Sunanda; Chandra, Goutam (Current Drug Discovery Technologies, 2021)
Background: The only remedy for up surging problem of antibiotic resistance is the discovery of antibacterial agents of natural origin. Objective: The present study was aimed at finding antibacterial potential of crude and solvent extracts of mature leaves of Plumeria pudica. Methods: Antibacterial activity of three different solvent extracts were evaluated in four human and four fish pathogenic bacteria by measuring the zone of inhibition and determining Minimum Inhibitory Concentration and Minimum Bactericidal Concentration values. Standard antibiotics were used as positive control. Preliminary phytochemical screening of most effective extract i.e., ethyl acetate extract, Fourier Transform Infra Red analysis and GC-MS analysis of the Thin Layer Chromatographic (TLC) fraction of ethyl acetate extract were done meticulously. All experiments were done thrice and analyzed statistically. Results: Crude leaf extracts and solvent extracts caused good inhibition of bacterial growth in all selected bacteria. Ethyl acetate extract showed highest inhibition zones in all tested strains with maximum inhibition (19.50±0.29 mm) in Escherichia coli (MTCC 739). MBC/MIC of the extracts indicated that all three solvent extracts were bactericidal. Preliminary phytochemical tests revealed the presence of tannins, steroids and alkaloids and FT-IR analysis revealed presence of many functional groups namely alcoholic, amide, amine salt and aldehyde groups. From the GC-MS analysis of TLC fraction of ethyl acetate extract, five different bioactive compounds e.g., 2,4-ditert –butylphenyl 5-hydroxypentanoate, Oxalic acid; allyl nonyl ester, 7,9-Ditert-butyl-1-oxaspiro(4,5)deca-6,9-diene- 2,8-dione, Dibutyl phthalate and 2,3,5,8-tetramethyl-decane were identified. Conclusion: Leaf extracts of P. pudica contain bioactive compounds that can be used as broad spectrum bactericidal agent.
Keywords: In-vitro bactericidal activity